Pengaruh Kualitas Konten Edukasi dan Promosi Diskon Terhadap Niat Beli Konsumen Pada Produk Glad2Glow di Jakarta Timur - Rani Sinaga; Teddy (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
The rapid growth of the beauty industry has intensified competition among skincare brands, requiring companies to develop communication and promotional strategies that effectively influence consumer purchase intention. Educational content can help consumers understand product benefits, ingredients, usage, and suitability, while discount promotions may create additional economic value and encourage purchasing decisions. This study aims to examine the partial and simultaneous effects of educational content quality and discount promotion on consumers’ purchase intention toward Glad2Glow products in East Jakarta. The study employed a quantitative approach with a descriptive and causal research design using a survey method. The research population consisted of Glad2Glow product users residing in the Administrative City of East Jakarta. Respondents were selected through simple random sampling, providing each member of the population with an equal opportunity to participate. Data were collected using a structured questionnaire and analyzed through multiple linear regression with the support of statistical software. Hypothesis testing involved the coefficient of determination, partial significance test, and simultaneous significance test. The findings indicate that educational content quality has a positive and significant effect on consumers’ purchase intention. Discount promotion also has a positive and significant effect on purchase intention. Simultaneously, educational content quality and discount promotion significantly influence consumers’ intention to purchase Glad2Glow products. These findings suggest that informative, credible, and relevant educational content, combined with attractive discount strategies, can strengthen consumer interest and improve Glad2Glow’s competitiveness in the beauty market.